Shear behaviour of RC beams strengthened using geosynthetic materials by external and internal confinement. (August 2021) - Majumder, Subhrasmita; Saha, Showmen
Abstract: The objective of the present article is to study the behaviour of shear deficient reinforced concrete (RC) beams strengthened with geosynthetic materials by the experimental and analytical investigation. Two types of geosynthetic materials viz. geogrid and geotextile were applied to strengthen the RC beam by external and internal confinement. In this experimental investigation, all the RC beam specimens tested under the three-point-bending load. The shear failure is noticed in the shear critical RC beams, which has turned into a flexural-failure after strengthening with geogrid and geotextile materials by external and internal confinement. A remarkable enhancement in load-carrying capacity, energy-dissipation capacity, ductility-factor, and post-yielding behaviour is observed in all the strengthened RC beams compared to the un-strengthened conventional specimens. Further, the performance of geogrid confined specimens on these parameters is better when compared to the geotextile confined RC beams, and it is maximum in the outer confined specimens. The economy index of all the geogrid and geotextile strengthened RC beam specimens is also increased in comparison with the conventional un-strengthened specimens. Hence, it is confirmed that geogrid and geotextile materials can be a very useful strengthening solution in the RC beam by external or internal confinement with very low cost. However, for new construction, these materials can be used as shear reinforcement instead of traditional reinforcing materials, which will be very cost-effective. Further, an analytical study is carried out to illustrate the ultimate load of all the RC beam specimens, where the analytical predictions are very close to the experimental findings and show very well agreement with the test results.